ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2013-2015 - Yuli Rianawati, 16.05.62.0023; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2018)
This study examines the Factor Analysis that affect the Firm Value. This research is conducted at Indonesia Stock Exchange by using property and real estate company which have go public. The population in this study is all companies listed on the Indonesia Stock Exchange in 2013 to 2015. The sample used in this study are property and real estate companies. The results of this study indicate that size has a positive not significant effect, profitability has negative significant effect, leverage has positive significant effect, investment decision has positive not significant effect, firm growth has not significant effect on firm value.Keywords: firm size, profitability, debt policy, investment decision, company growth, and firm value.